2016
DOI: 10.1007/s10096-016-2614-z
|View full text |Cite
|
Sign up to set email alerts
|

Infections in travellers returning to Turkey from the Arabian peninsula: a retrospective cross-sectional multicenter study

Abstract: Mass gatherings pooling people from different parts of the world-the largest of which is to Mecca, Saudi Arabia, for Hajj-may impose risks for acquisition and dissemination of infectious diseases. A substantial number of pilgrims to Hajj and Umrah are Turkish citizens (456,000 in 2014) but data are lacking on scale of the problem. We did a retrospective cross-sectional multicenter study in Turkey to explore the range of infections among inpatients who had recently returned from the Arabian Peninsula. Our inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…A recent retrospective cross-sectional multicenter study of 185 Turkish inpatients (87.5% were pilgrims) who returned to Turkey from the Arabian Peninsula countries between 2012 and 2014 reported a slightly higher prevalence of acute tracheobronchitis (13.6%) [64]. In addition, in this study, pneumonia was among the most common clinical diagnosis among the hospitalized Hajj patients and represented about half of diagnoses [64]. As pneumonia remains a major concern in critically ill patients, most of them reported the prevalence of pneumonia among pilgrims [57,59,60,[62][63][64][65][66][67][68][69][70][71], with reported rates ranging from 0.2% in 2008 in 13 randomly selected Mina primary health care centers [59,60] to 54.8% in 2004 in two ICU in Mecca [68] (Table 3).…”
Section: Hospital-based Studies Addressing the Prevalence Of Respiratmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective cross-sectional multicenter study of 185 Turkish inpatients (87.5% were pilgrims) who returned to Turkey from the Arabian Peninsula countries between 2012 and 2014 reported a slightly higher prevalence of acute tracheobronchitis (13.6%) [64]. In addition, in this study, pneumonia was among the most common clinical diagnosis among the hospitalized Hajj patients and represented about half of diagnoses [64]. As pneumonia remains a major concern in critically ill patients, most of them reported the prevalence of pneumonia among pilgrims [57,59,60,[62][63][64][65][66][67][68][69][70][71], with reported rates ranging from 0.2% in 2008 in 13 randomly selected Mina primary health care centers [59,60] to 54.8% in 2004 in two ICU in Mecca [68] (Table 3).…”
Section: Hospital-based Studies Addressing the Prevalence Of Respiratmentioning
confidence: 99%
“…On the contrary, lower prevalence rates of bronchitis were reported during the Hajj (1.4%-9.6%) [59][60][61][62][63]. A recent retrospective cross-sectional multicenter study of 185 Turkish inpatients (87.5% were pilgrims) who returned to Turkey from the Arabian Peninsula countries between 2012 and 2014 reported a slightly higher prevalence of acute tracheobronchitis (13.6%) [64]. In addition, in this study, pneumonia was among the most common clinical diagnosis among the hospitalized Hajj patients and represented about half of diagnoses [64].…”
Section: Hospital-based Studies Addressing the Prevalence Of Respiratmentioning
confidence: 99%
“…More importantly, most global MERS cases were linked to travel to the Arabian peninsula. Although all surveillance studies during Hajj did not reveal any MERS‐CoV infection among pilgrims, serological testing showed positivity in one Turkish pilgrim who suffered from severe pneumonia and died upon ICU admission in Turkey . Similarly, confirmed cases were reported from Dutch pilgrims returning home from the minor pilgrimage “Umrah” .…”
Section: Introductionmentioning
confidence: 97%
“…Another important driver of spreading and acquiring respiratory pathogens during Hajj is the great diversity of inbound viruses from around the world that can potentially spread among the immunologically naive hosts. In fact, acute respiratory infections are very common during Hajj and represent the leading cause of the most hospitalizations . It has been suggested that more than one‐third of pilgrims will suffer from respiratory symptoms during Hajj mostly due to the respiratory viruses .…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter study conducted in Turkey by Erdem et al [60] investigated infections diagnosed in pilgrims who traveled to Arabia. Respiratory tract infections (91%) and gastroenteritis (7%) were the most common diagnoses.…”
Section: Approach To Posttravel Infectionsmentioning
confidence: 99%